KAIZEN CULTURE: DOUBLE THE GOOD, HALF THE BAD PERSPECTIVE OF ELECTRICAL & ELECTRONICS MANUFACTURERS - Kong Siew Mui; Rajendran Muthuveloo; Josephine Chan Ie Lyn (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Kaizen culture is extremely crucial for manufacturing companies operating in the electrical and electronics (E&E) industry in Malaysia. The productivity gains of the E&E industry is on a gradual downward trend, made worse by the current Covid-19 pandemic crisis. However, this trend could be arrested if kaizen culture is nurtured within the organization. Having kaizen culture will foster a culture of continuous improvements which is essential for productivity, thus increasing operational performance. The main aim of this study is to examine the impact of kaizen culture on operational performance as well as establishing the key attributes of kaizen culture. The data was collected through a survey conducted on 248 E&E manufacturing companies of which 127 responded. Results indicated kaizen culture having a significant positive influence on operational performance. Among the four key attributes of kaizen culture, management support ranked the highest, while kaizen promotion office ranked the lowest. For practitioners, this study confirmed that kaizen culture is vital for the optimization of operational performance to increase global competitiveness.